Acknowledging and Learning from Different Types of Failure - Naomi Vernon; Jamie Myers (SAGE Publishing, 2021)
The challenges faced in sanitation and hygiene programmes are numerous and complex. Failures are inevitable. From our experience of working on rapid action learning and research in this sector we have found that when mistakes are shared they are usually those which were uncontrollable and unanticipated i.e. somebody else's fault. In this perspectives piece we propose a typology of failure alongside criteria for research and learning processes that prioritises timeliness, relevance and actionability. We argue that these can be used together to identify and reflect on failures (and successes) quickly. We provide some practical suggestion for different stakeholders to support a shift towards a more open and reflexive sector, where all types of failures can be shared broadly.